„Die Transvestiten haben das Wort“: the politics of gender variation, sexual distinction and morality in the transvestite magazine Das 3. Geschlecht - Hazel Rhodes (Gender, 2023)
This article analyzes the Weimar-era transvestite magazine Das 3. Geschlecht (1930–1932), originally published by Friedrich Radszuweit, and assesses the affective and political qualities of the transvestite public culture that it organized. Scholars have shown how transvestite counter publics emerged in Germany alongside gay and lesbian collectives, spurred by the development of a queer press and urban social networks and tempered by a politics of respectability. As Das 3. Geschlecht shows, certain transvestites responded to the new publicity around transvestism by turning to modesty, privacy and inconspicuousness, not necessarily to public resistance or visibility as trans*. My argument explains this tendency toward gender conservatism, heterosexism, and middle-class conventions like domesticity and decency by emphasizing how this space operates as an intimate public, building on the concept by Laurent Berlant. Focusing on normative and ‘generic’ mediations of the experience of transvestism, I explore how the magazine’s public sought to shape the conditions for living as a transvestite in Weimar society, when the norms for trans personhood were still being conceived and disputed. Aspirational fantasies of gender and sexual normalcy and seamless belonging in middle-class society prove more significant to these mediations than oppositional or emancipatory politics.